Nitrogênio e água no crescimento de cultivares de alface - Cardoso, Francieli Lima (2016)
The goal of this research was to determine relationships between nitrogen (N) and water availabilities and growth of lettuce plants. In the first chapter, experiments were conducted in autumn-winter and spring-summer 2013 to determine growth, development and N accumulation in plants of cv. Stella and Veneranda grown under N concentrations of 5.72; 7.72; 9.72; 11.72 and 13.72 mmol L-1. Results showed that the current practice of using high nitrogen fertilization rates to maximize growth of lettuce plants has to be adapted to cultivars and growing periods. The second chapter was composed by two experiments inside a polyethylene greenhouse in 2013 and a third calibration experiment in the field conducted in 2014. In the greenhouse, cv. Stella and Veneranda plants were supplied with nutrient solutions at N concentrations of 5.72; 7.72; 9.72; 11.72 and 13.72 mmol L-1 in two growing periods. Relationships between the nitrogen accumulation and vegetative growth of plants were fitted, in order to adjust nitrogen fertilization to demand by plants. The field calibration experiment used the Stella cultivar and N fertilization estimated by those relationships. A nitrogen fertilization schedule was outlined based on the number of leaves for two growing periods. It was concluded that relationships among growth, development and nitrogen accumulation can be used for splitting nitrogen fertilization during growth of lettuce crops. In the third chapter, experiments were conducted from January 13 to February 4 in summer and from April 24 to June 5, 2015, in autumn, to search for relationships among substrate volume, N concentration and fertigation method on growth of lettuce plants. Treatments were two pot sizes, 1.7 (big) and 0.41 dm3 (small), two methods of fertigation, drip and subirrigation, and two concentrations of N in the nutrient solution, 6.23 and 10.23 mmol L-1. The water distribution in the top, middle and bottom section of big pots differed in both fertigation methods. In summer higher growth of plants was recorded on drip fertigated plants. The N concentration affected root growth in small pots, being lower on plants supplied with the higher N concentration. Results showed that high N concentration in a small volume of rooting medium reduces shoot growth. Its was concluded that the management of nitrogen fertilization should take into account the extraction of the nutrient during the plant growth and development period, suitable volume of root medium and uniform distribution of water and nutrients.